PENGHILANGAN TINTA PADA KERTAS THERMAL BEKAS : PENGARUH KONSISTENSI DAN KONSENTRASI PENDISPERSI FLOTASI - Sulastri Dewanti, Elisabet Aprilyanti, Taslim (Universitas Sumatera Utara, 2014)
Recycling of wastepaper is a solution for paper industry to overcome the scarcity and the limited presence of the virgin pulp sources. Thermal paper is a highly engineered product coated with a thermal sensitive layer that reacts in the presence of heat to create the printed image. The purpose of this research is to study the effect of pulp consistency and dispersant concentration on the removal of ink in the thermal paper. There are 3 steps in this research which are immersing, pulping and flotation. The results of this research were measured according to TAPPI and SNI to determine the brightness and tensile strength of the recycled paper, respectively. The excellent conditions were obtained at pulp consistency of 0.8%, dispersant concentration of 1.5%, flotation temperature of 50 °C and flotation time of 40 minutes. In these conditions, the brightness was 72,17% and tensile strength was 3.7 kN/m.